2020
DOI: 10.22225/jj.7.1.1653.53-64
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Commitments Mediates The Effect of Competence on Employee Performance in PT. Bali Tangi Spa Production

Abstract: Business development and competition will continue to increase from time to time following the development of information technology, so each company must continue to be creative and innovate by continuously improving the quality of its human resources. Human resources are one of the most important assets in a company or organization, as sophisticated and as complete as any other aspect of the organization but without the support of competent human resources, the organization will not operate well. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…The same holds true for the claim that dedication to a solid organization can boost one's performance within the company [61], [62]. Authoritative responsibility is the level at which people take on the qualities and objectives of the association and relate to them in satisfying their work liabilities [63].…”
Section: π‘Œ = 𝑖1 + 𝑐𝑋 + 𝑒1mentioning
confidence: 90%
“…The same holds true for the claim that dedication to a solid organization can boost one's performance within the company [61], [62]. Authoritative responsibility is the level at which people take on the qualities and objectives of the association and relate to them in satisfying their work liabilities [63].…”
Section: π‘Œ = 𝑖1 + 𝑐𝑋 + 𝑒1mentioning
confidence: 90%
“…In contrast to the research conducted by (Kawangung et al, 2020) concluded that competence has no significant effect on performance. Previous studies have found the effect of competence on organizational commitment, such as research conducted by (Suantara et al, 2020), (Sumarsi &Rizal, 2021) and(Aryani et al, 2021) which concluded that competence has a positive and significant effect to organizational commitment. However, research conducted by (Yamali, 2018) and (Ngatimun et al, 2021) concluded that competence has a partially insignificant effect on organizational commitment.…”
Section: Introductionmentioning
confidence: 94%
“…Penelitian yang dilakukan oleh (Rika & Nurhayati, 2017), (Vernon et al, 2019), (Adam & Kamase, 2019), (Noor & Limakrisna, 2019), (Sturm et al, 2017), (Amdani et al, 2019), (Noel et al, 2017), (Jeffrey & Dinata, 2017), (Saengchai et al, 2019) menyatakan bahwa kompetensi memberikan pengaruh signifikan terhadap kinerja. Berbeda halnya dengan penelitian yang dilakukan oleh (Berdicchia & Masino, 2019), (Adianita et al, 2017), (Suhardi & Syaifullah, 2017), (I Ketut Suantara et al, 2020) menyatakan bahwa kompetensi memberikan pengaruh tidak signifikan terhadap kinerja. Berdasarkan studi empiris dapat disimpulkan bahwa kompetensi memberikan pengaruh terhadap kinerja.…”
Section: Kompetensi Terhadap Kinerjaunclassified